Utilisation of beds on the general medical unit by 'non‐acute medical' patients: a retrospective study of incidence and cost in two Tasmanian regional medical hospital units. Issue 2 (February 2014) - Buist, M. D.; Jaffray, L.; Bell, E.; Hanna, L.; Weinstein, P.; Kumar, S.; Grimmer, K.
Abstract Background Demand for healthcare services threatens to overwhelm the Australian healthcare system. Public hospitals have the largest component of expenditure growth and as such represent the largest opportunity for efficiency gains. Utilisation of inpatient hospital beds and in particular those on general medical units has not been studied in Australia. Aim To undertake a retrospective patient medical record review of 200 sequential admissions to the medical wards in two regional Tasmanian hospitals to determine the incidence of non‐acute medical patient admission to the medical unit, and the subsequent days in hospital that were not required for medical reasons. The cost of these days was estimated. Results Sixteen patient admissions (8%) could not be justified on medical grounds. Forty‐eight (24%) patient admissions had at least one day hospital day that could not be justified on medical grounds. Of the 1438 total bed days, 475 (33%) were for non‐medical reasons. The estimated cost of those non‐medical bed days for this cohort was $764 800. Conclusions The incidence of non‐acute medical admissions and non‐acute medical bed days to the medical unit and associated cost was significant. Further research is needed to design alternative care provision for such patients particularly in regional Australia. The potential savings to the Australian healthcare system could be significant.